Achievement Motivation and Its Relationship with Selected Demographic Variables among a Sample of University Students - Yarwaisi, Dr. Luqman Mohammed Ahmad YarWaise (Sulaimani Journal for Humanities, 2025)
This study aims to examine academic achievement motivation among students of the College of Humanities Science – Said Sadiq, University of Sulaimani, and its relationship with several demographic variables, including gender, field of study, place of residence, and family income. Achievement motivation is considered a critical psychological factor that directly affects students’ academic performance. The researcher employed a descriptive-analytical method due to its effectiveness in describing phenomena and measuring statistical relationships accurately. A random sample of 192 students was selected, consisting of 92 female and 42 male students. Data were analyzed using various statistical tools, including the arithmetic mean to assess reliability, inferential tests to examine differences between variables, and statistical software for precise and objective analysis. The results indicated statistically significant differences in achievement motivation based on gender, field of study, and place of residence. The study recommends providing psychological and educational support to students and considering individual differences arising from demographic factors when designing academic programs, as these factors directly impact academic performance and enhance students’ adaptability and success. Among the key findings, the study revealed that university students exhibit high levels of achievement motivation, with notable differences according to gender, field of study, and place of residence. Finally, the researcher provided a set of recommendations and suggestions to further support student development.
Keywords: Achievement motivation; academic; relationship; students; university; demographic variables